Estudio del rendimiento financiero en la cooperativa de Ahorro y Crédito San Antonio agencia La Unión durante el periodo 2019 – 2020 - Badillo Almeida, Dayanna Belén (2022)
The present study is directed to the analysis of the financial situation that the cooperative had during the period 2019 - 2020, taking into account the factors that occurred in the last year, that case study will be carried out in the San Antonio Savings and Credit Cooperative Ltda. Agency La Unión, where the impact and incidence of the pandemic on the economic solvency, financial performance and liquidity of this entity will be shown. The San Antonio Cooperative is dedicated to promoting the quality of life of its members through the financial services that this entity offers, thus being a main source of financing for its members' projects. The fundamental objective when carrying out this case study is to analyze the financial performance that the entity had in the pre- and post-pandemic period, which affected its liquidity, profitability and income and expenses so much, where some financial ratios were applied. The Covid-19 pandemic during the 2020 period has touched different points of the economy and finances around the world and the San Antonio cooperative was not exempt from this blow, in year-on-year terms the popular and supportive superintendence tells us that the deposits and the credit portfolio in the cooperatives of Ecuador have been superior in 2020, a year hit by the pandemic, the cooperatives present an increase in their credit and deposit portfolio compared to the 2019 period. The analysis of liquidity within financial institutions is very important, because it allows us to maintain control of its profitability and solvency.